Spatial and temporal variations in turbidity on two inshore turbid reefs on the Great Barrier Reef, Australia - Browne, Nicola; Smithers, S.; Perry, C. (Springer Verlag, 2013)
This study describes the natural turbidity regimes at two inshore turbid reefs on the central Great Barrier Reef where wind-driven waves are the main agent of sediment resuspension. Many corals on inshore turbid reefs have adapted to high and fluctuating turbidity, however, anthropogenic activities such as dredging are speculated to produce larger and more prolonged turbidity events that may exceed the environmental tolerance and adaptive capacity of corals on these reefs. Natural turbidity regimes must be described and understood to determine whether and when coral communities on inshore turbid reefs are at risk from anthropogenically elevated turbidity, but at present few baseline studies exist. Here, we present turbidity data from (a) Middle Reef, a semi-protected reef located between Magnetic Island and Townsville and (b) Paluma Shoals, a reef exposed to higher energy wind and waves located in Halifax Bay. Instruments were deployed on both reefs for 16 days to measure spatial and temporal variations in turbidity and its driving forces (waves, currents, tides). Locally driven wind waves were the key driver of turbidity, but the strength of the relationship was dependent on wave exposure. Turbidity regimes thus vary markedly over individual reefs and this is reflected in community assemblage distributions, with a high abundance of heterotrophic corals (e.g. Goniopora) in reef habitats subjected to large fluctuations in turbidity (>100 NTU).A turbidity model developed using local wind speed data explained up to 75 % and up to 46 % of the variance in turbidity at Paluma Shoals and Middle Reef, respectively. Although the model was based on a brief two-week observational period, it reliably predicted variations in 24-h averaged turbidity and identified periods when turbidity rose above ambient baseline levels, offering reef managers insights into turbidity responses to modified climate and coastal sediment delivery regimes.